(untitled) (Asian Education Studies, 2021)
With the continuous maturation of China’s social network information technology, the arrival of the media era has greatly changed the environment of Ideological and political education in Colleges and universities, and increased the difficulty of education. In order to improve the effect of ideological education, colleges and universities take the initiative to explore new working methods of Ideological and political education, so as to promote the all-round development of students.